NFAT as a Biomarker and Therapeutic Target in Non–Small Cell Lung Cancer–Related Brain Metastasis - Peng, Lu; Tao, Yihao; Wu, Rui; Su, Jing; Sun, Maoyuan; Cheng, Yuan; Xie, Zongyi; Mao, Jinning; Zhan, Xiaohui; Liu, Guodong (Frontiers in Oncology, 2021)
Background: Brain metastases (BMs) are associated with poor prognosis and significant mortality, and approximately 25% of patients with non–small cell lung cancer (NSCLC) develop BMs. The present study was aimed to understand the relationships between BM and NSCLC and reveal potential biomarkers and therapeutic targets in NSCLC-related BM. Methods: The differentially expressed genes (DEGs) expressed during NSCLC and BM development were predicted by bioinformatics analysis, and the expression of the upstream transcription factor nuclear factor of activated T cells (NFAT) was confirmed as a differential gene expressed in both NSCLC and BM. In addition, the expression of proteins encoded by these DEGs was verified by immunohistochemical experiments examining normal lung tissue, lung cancer tissue, and brain metastasis tissue from 30 patients with NSCLC related BM. Results: The co-DEGs interleukin (IL)-11, cadherin 5 (CDH5) and C-C motif chemokine 2 (CCL2) link NSCLC and BM in the Gene Expression Omnibus (GEO) database, and NFAT may target the expression of these co-DEGs. In the GEO database, NFATc1 and NFATc3 were significantly downregulated in NSCLC tissues (P < .05), whereas NFATc1, NFATc2, NFATc3, and NFATc4 were significantly downregulated in BMs (P < .05). Consistent findings were observed in the immunohistochemical analysis. Conclusion: NFATc1 and NFATc3 may play important roles in the occurrence of NSCLC and BM by regulating IL-11, CDH5, and CCL2